INCREASE OF COMPETITIVE SUSTAINABLE IN AGRICULTURAL ENTERPRISES BY DIVERSIFICATION - Лозинська, Т. М.; Чаговець, О. В. (Scientific Progress & Innovations, 2014)
The topicality of the analysis of readiness to diversify agricultural enterprises has been grounded to improve their competitive sustainability. Tendencies of development of agricultural market have been explored and motives for diversification of agricultural enterprises have been established. The results of applying the method of three-dimensional morphological classification have been showed to identify the state of readiness of enterprises to diversify. The content of causal relationships resulting from the combination of business processes with different parameters has been characterized. Attention is paid to the subjectivity of the agricultural enterprises in the process of diversification.